The Effect of STEM-Project-based Learning on Self-Efficacy in High School Chemistry Learning - Atifah, Alya; Sari, Rr. Lis Permana (Universitas Pendidikan Mandalika, 2025)
This research aims to determine the effect of STEM integrated project-based learning model on students' self-efficacy in learning chemistry. This research method uses a quasi-experiment with a pretest-posttest design consisting of one experimental class and one control class. The experimental class applied the STEM integrated project-based learning model and the control class applied the cooperative learning model. The instrument used is a self-efficacy scale which includes 5 aspects, namely, motivation, task orientation, confidence, perseverance, and problem solving. The data obtained were analyzed using descriptive statistics and inferential statistics. Inferential statistics in the form of independent t-test and paired sample t-test. Based on the analysis conducted, there is a significant difference in the self-efficacy of students between the experimental class and the control class and there is a difference in self-efficacy before and after the STEM integrated PjBL learning model is applied.Â The increase in the N-Gain score obtained from the experimental class was higher than the control class seen from the increase in all aspects of self-efficacy. The implications of this research are expected to be able to be a new view and reference for teachers in applying the STEM-integrated PjBL model to increase students' self-efficacy in learning chemistry.